1991
DOI: 10.1080/00140139108964856
|View full text |Cite
|
Sign up to set email alerts
|

The objective measurement of pain using a motor-performance task

Abstract: An objective method for measuring endogenous pain in the wrist which originates in cervicobrachial disorders was improved. The method employed the plate-pushing task, which was reported previously (Taniguchi and Satow 1988a, b). The first improvement was achieved by introducing a load to be placed on the wrist while subjects were pushing the plate. In this way, it became easier to induce pain caused by disorders in the wrist. Another improvement was a new procedure by which a subject was told to change her pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…It showed the improvement of pain control following general surgical procedures (10, 20, 25). The pain assessment was the primary postoperative outcome as defined by visual analogue score (2, 3, 26) . Secondary clinical outcome included postoperative nausea and vomiting.…”
Section: Discussionmentioning
confidence: 99%
“…It showed the improvement of pain control following general surgical procedures (10, 20, 25). The pain assessment was the primary postoperative outcome as defined by visual analogue score (2, 3, 26) . Secondary clinical outcome included postoperative nausea and vomiting.…”
Section: Discussionmentioning
confidence: 99%
“…Schneider & LoBiondo-Wood, 1992, found that children's reports correlated well with parental observations but not with nurses' observations), activity levels or overt motor behaviour. Taniguchi & Satow (1991) employed a plate-pushing task to measure wrist pain.…”
Section: Painmentioning
confidence: 99%